2015
DOI: 10.1007/s12070-015-0913-9
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Laryngeal Exposure in Microlaryngoscopy: Can it be Predicted Preoperatively?

Abstract: The aim of the present study was to identify preoperative clinical predictors for difficult laryngeal exposure (DLE) and to define a simple grading system for laryngeal exposure. This is a prospective descriptive study carried out in a tertiary teaching hospital in South India. Patients above 18 years undergoing microlaryngoscopy had presurgical evaluation of 11 physical parameters. Grading of Modified Cormack-Lehane Score (MCLS) and rigid laryngoscopy were done during procedure. On logistic regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…For Pinar et al, this correlation was found with measurement of the HMD and SMD in the full extension position, which are related to the degree of retrognathia and length of the neck 8 . However, in other studies, those measures were not good predictors for DLE 9 , 15 .…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…For Pinar et al, this correlation was found with measurement of the HMD and SMD in the full extension position, which are related to the degree of retrognathia and length of the neck 8 . However, in other studies, those measures were not good predictors for DLE 9 , 15 .…”
Section: Discussionmentioning
confidence: 60%
“…Hekiert et al 14 proposed a visual analog score (VAS) of 1 to 10 assessed by the laryngologist, with 1 being the least difficult and 10 being the most difficult. However, although this definition varies according to the authors, the majority agree that exposure limited to the posterior third or less of the vocal cord defines DLE 9 , 12 , 13 , 15 . We applied the protocol proposed by Hsiung, which consists of evaluating laryngeal exposure after putting the patient in the sniffing position, external counterpressure and changing to a smaller laryngoscope if the exposure is not complete 9 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations